CULTURAL AND MORPHOLOGICAL CHARACTERIZATION OF ALTERNARIA BRASSICAE OF MUSTARD IN ALLAHABAD UTTAR PRADESH - SHAILENDRA KUMAR; S. M. PRASAD; H. K. KEHRI (The Journal of Research ANGRAU, 2025)
Alternaria brassicae isolates were collected from the black leaf spot of mustard during the winter season (2019-2021) in the various regions of the Allahabad district. In vitro, results show  significant variability in growth pattern, sporulation, conidial length, width, and septa number in different culture media, temperature, pH, and relative humidity. The conidial length of the isolates  II-2C20, III-5C20, V-2A20, V-7A20, and I-6A1y21 was the shortest, measuring 14 ìm. The isolate  I-4B21 and II-7C21 had the longest conidial length, ranging from 72 ìm to 72.8 ìm, respectively. The average conidial length ranged from 30.1 ìm to 50.9 ìm, with mustard isolate I-6A1y21 having  the lowest value and I-4B21 having the highest. The highest average width was 15.86 ìm. The best mediums for 31 isolates were Potato Dextrose Agar, Meal Agar, Corn Meal Agar, Czapex dox agar, Carrot meal agar, and V-8 juice Agar. The highest radial growth was shown in the OMA medium by I-6A1y21 isolates, while the lowest growth was shown in the CA medium by II-7C21 and II-8B21 isolates. Out of all of them, the isolate I-6B121 sporulated the most (41.75x105/ml)  whereas the isolate I-4A21 sporulated the least (0.5x105/ml) in OMA and CA medium. The radial growth and sporulation are optimal at 24°C, moderate at 18°C and 30°C, and lowest at 6°C and 36°C. Isolate III-3B20 and II-5C20 showed the least average radial growth and sporulation at all pH levels, while isolate I-6A1y21 showed maximum growth. The pH 7 is more favourable for radial growth and sporulation. The study found that radial growth and sporulation increased in relative humidity between 80-100%, while decreased in 20-40%, with isolate I-6A1y21 showing the highest growth while II-UN120 and III-5C21 exhibited the least. Among the 31 isolates, 9 isolates II-UN120, IV-5C20 I-4A21, I-6B21, I-6A1y21, II-8B21, III-6C21, IV-4B21, and IV- 6AY21 were found to be high degree of infection as the spot produced by them were more than 10 mm in diameter. Statistical analyses were conducted using Microsoft 365 Excel and SPSS 28.0 version on Windows 10, using ANOVA and Duncan’s multiple range test of homogeneity at a P=0.05 level.